2021
DOI: 10.1108/ijhma-08-2021-0093
|View full text |Cite
|
Sign up to set email alerts
|

Early impact of Covid-19 on private sector employees finance homeownership in Kingdom of Saudi Arabia

Abstract: Purpose For almost two years, the economic shocks and financial uncertainty created by the Covid-19 pandemic have affected all sectors. The private sector employees may be the worst hit. This is because of the lockdown across many countries, including the Kingdom of Saudi Arabia (KSA), leading to income irregularities. Studies exploring private-sector employees concerning housing finance for the houses purchased and how the lockdown has affected their sources of income for repayment plans are scarce. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
4
4
0
Order By: Relevance
“…Between 1 July and 30 August 2021, ten virtual interviews were conducted in three KSA cities (Medina, Riyadh and Alqassim), and saturation was achieved after further exploration with the ten engaged participants. This is in line with Alharbi (2021) that adopted these cities in a similar study that involved Covid-19 and housing finance because they are among the commercial hubs in KSA. The study objectives were achieved via the semi-structured questions and findings thematically presented (Stysko-Kunkowska, 2014; Ebekozien et al , 2021).…”
Section: Methodssupporting
confidence: 84%
“…Between 1 July and 30 August 2021, ten virtual interviews were conducted in three KSA cities (Medina, Riyadh and Alqassim), and saturation was achieved after further exploration with the ten engaged participants. This is in line with Alharbi (2021) that adopted these cities in a similar study that involved Covid-19 and housing finance because they are among the commercial hubs in KSA. The study objectives were achieved via the semi-structured questions and findings thematically presented (Stysko-Kunkowska, 2014; Ebekozien et al , 2021).…”
Section: Methodssupporting
confidence: 84%
“…This sub-section focuses on the possible impact of the COVID-19 crisis on affordable housing finance in Vision 2030. The pandemic has changed the pattern of the housing market and the life of intending house owners globally, especially those who are yet to complete their housing finance (mortgage) payments (Alharbi, 2021). In the United States of America, an estimated rate of 44.2 m joblessness erupted as one of the outcomes of general lockdown across the nation (United States Department of Labour, 2020).…”
Section: Impact Of Covid-19 On Affordable Housing Finance In Vision 2030mentioning
confidence: 99%
“…This created an economic recession, by extension, affecting the housing market. Alharbi (2021) opined that a job applicant could not pay back housing loans to the mortgage institution until there is an employment. Ettman et al (2021) reported in early April 2020, 40 states were restricted and 39 states shut down nonessential businesses.…”
Section: Impact Of Covid-19 On Affordable Housing Finance In Vision 2030mentioning
confidence: 99%
See 2 more Smart Citations